A practical approach to Dideoxy-1, 4- and 1, 5-iminopentitols from protected sugar hemiacetals. (1st December 2019) - Jaszczyk, Justyna; Li, Sizhe; Cocaud, Chloé; Nicolas, Cyril; Martin, Olivier R.
Abstract: The convenient and straightforward preparation of dideoxy-1, 4- and 1, 5-iminopentitol derivatives from protected sugar hemiacetals by way of N-tert -butanesulfinyl glycosylamines and open-chain aminoalditols is reported. The synthetic procedure is a method of choice for the making of these important scaffolds of biological interest. Graphical abstract: Image 1 Highlights: Short, general and convenient method. Synthesis of dideoxy-1, 4- and 1, 5-iminopentitols from protected sugar hemiacetals. Use of a sulfinyl glycosylamine as an aldose imine equivalent. Moderate to good overall yields (24–55%) obtained through two reaction sequences of 2.5 and 3.5 h.